Penerapan Aplikasi Restock Barang Berbasis React Native untuk Pengelolaan Stok Usaha Fotokopi di Kalituk - Mayla Fayza Keishya; Vidi Sandi (Switch : Jurnal Sains dan Teknologi Informasi, 2026)
Inventory management in photocopy businesses in Kalituk is still predominantly carried out manually, resulting in various operational challenges such as recording errors, delays in restocking, inaccurate stock information, and discrepancies between recorded and actual inventory levels. These issues can affect business efficiency and hinder the smooth execution of daily operations. This study aims to implement a React Native-based restock application to improve the efficiency, accuracy, and effectiveness of inventory management in photocopy businesses. The system was developed using a structured design approach that includes the creation of a Context Diagram, Data Flow Diagram (DFD), Entity Relationship Diagram (ERD), and Activity Diagram to model and analyze system processes comprehensively. The developed application provides features for recording incoming and outgoing stock, monitoring inventory availability, managing inventory data in real time, and facilitating faster decision-making regarding restocking activities through mobile devices. System testing was conducted to evaluate functionality and usability. The results demonstrate that the application is capable of simplifying inventory recording and restocking processes, minimizing human errors in data entry, improving inventory monitoring, and increasing operational efficiency. In addition, the mobile-based platform enables users to access inventory information more flexibly and conveniently. Therefore, the implementation of the React Native-based restock application can serve as an effective solution for supporting more organized, accurate, and modern inventory management practices, ultimately contributing to improved business performance and operational sustainability in photocopy enterprises.